Depositional architecture and evolution of deep-water base-of-slope and slope channel complexes in a passive-margin setting: Isaac Formation, Windermere Supergroup (Neoproterozoic), southern Canadian Cordillera - Ugueto, Lilian L. Navarro (University of Ottawa (Canada), 2006)
The Isaac Formation in the Neoproterozoic Windermere Supergroup crops out in the Castle Creek South area (southwestern Canadian Cordillera) and consists of a more than 1.2 km-thick, laterally continuous slope deposit formed along the ancestral passive margin of western North America. Within the study area, six channel complex sets have been recognized, of which two, named informally Channels 1 and 3, are the focus of this study. Channel 1 exposes an oblique section of base-of-slope channel deposits, whereas Channel 3, at least in its lower part, is a flow-transverse section. Channels 1 and 3 are 200-300 m thick and laterally extend over 1.1 km, and were initiated following two major falls of relative sea level. Detailed relationships between the intrachannel facies, architecture and geometry within both complex sets indicates that each comprises several vertically-stacked channel complexes that locally are separated by thin-bedded, mudstone-dominated turbidites interpreted to represent channel-abandonment deposits. Each channel complex consists of several channel units, which, in turn, are composed of multiple channel fills. Channel fills are up to 30 m thick and show different infill geometries (amalgamated, semi-amalgamated or layered, non-amalgamated and accretionary), exhibiting systematic lateral changes in fill from channel axis to channel margin. Multistory and multilateral fills in Channels 1 and 3 record a complex repetitive history of channel incision/bypass, aggradation, deactivation, migration and reincision. These erosional and depositional episodes are the result of changes in the equilibrium channel profile, flow parameters, and/or eustatic fluctuations.
Keywords: Geology.